The mechanism of intramolecular halogen bonding enhanced the quantum efficiency of ultralong organic phosphorescence in the aggregated state. Issue 37 (20th September 2022) - Liu, Songsong; Gao, Yang; Zhang, Kai; Liu, Shulei; Lan, Hao; Lin, Lili; Wang, Chuan-Kui; Fan, Jianzhong; Song, Yuzhi
Abstract : The mechanism of intramolecular halogen bonding enhancing the quantum efficiency of ultralong organic phosphorescence is revealed based on first-principles calculations. Abstract : Ultralong organic phosphorescence (UOP) has broad application prospects in many fields, but realizing its high quantum efficiency is still full of challenges. One of the main reasons is that the internal luminescence mechanism is unclear and theoretical investigations to reveal the inner structure–property relationship are highly desired. Herein, the internal mechanism of halogen bonding enhancing the quantum efficiency of UOP is studied through the combination of quantum mechanics and molecular mechanics methods coupled with the thermal vibration correlation function (TVCF) method. Geometric and electronic data are obtained by density functional theory (DFT) and time-dependent density functional theory (TD-DFT) calculations. Transition properties, energy gaps, intermolecular interactions, excited state dynamics as well as Huang–Rhys factors and reorganization energies are analyzed in detail. The results show that the high phosphorescence quantum efficiency benefits from the fast intersystem crossing (ISC) process and the slow non-radiative decay process. The halogen bonding, which cooperates with the effects of aromatic carbonyl and heavy atoms, not only accelerates the ISC rate by increasing the spin–orbit coupling effect, but also restricts the molecular motion and reduces the non-radiative energy consumption. Furthermore, through wise molecular design, an efficient UOP molecule with fast ISC and slow non-radiative decay rates is proposed. This work provides an insight into realizing efficient UOP emission via intramolecular halogen bonding.